Additional flow cytometric studies for differential diagnosis between Burkitt lymphoma/leukemia and B-cell precursor acute lymphoblastic leukemia. (January 2021) - Demina, Irina; Voropayev, Alexander; Semchenkova, Alexandra; Zerkalenkova, Elena; Olshanskaya, Yulia; Samochatova, Elena; Novichkova, Galina; Miakova, Natalia; Maschan, Alexey; Popov, Alexander
Highlights: Some cases of Burkitt leukemia/lymphoma need distinguishing from BCP-ALL. Additional cytometric markers can add relevant information to conventional studies. CD58 is a reliable marker for distinguishing between Burkitt lymphoma and BCP-ALL. Differences in CD38 and CD44 expression have no diagnostic implication. Cytometric assessment of proliferative activity can help for differential diagnosis. Abstract: The differentiation between Burkitt lymphoma/leukemia (BL) and B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is sometimes complicated. Laboratory findings that favor BL (e.g., surface expression of μ heavy chain and/or one of the light chains of immunoglobulin, FAB L3 morphology of blasts, MYC gene rearrangements) are not always present simultaneously. Our previous work demonstrated that BL differed from Ig(+) BCP-ALL by expression of Ig and other surface markers. In the current study, we have evaluated additional flow cytometric markers for reliable differentiation between BL and BCP-ALL. Among three studied surface antigens (CD44, CD38, CD58), only CD58 demonstrated significantly higher expression in BL as compared to BCP-ALL. Moreover, BL cases were associated with an increased level of Ki-67 and a higher percentage of cells in the S-phase of cell cycle. These two features reflect an aggressive proliferative potential of BL. Thus, when BL is suspected and results of surface Ig evaluation are controversial, the flow cytometric analysis of CD58, Ki-67 and cell cycle could assist in the differential diagnosis.